Characterization of a soft pneumatic actuator using fe modelling - Torres Atencia, Sharonluz Steffi (2021)
Actuators are devices that provides controlled changes regarding their displacement and position. They can be triggered by different inputs, one of them being fluids. Pneumatic actuators are commonly used in different areas. Rigid pneumatic actuators present multiple disadvantages, in size, weight, etc. limiting the application in other areas like soft robotic and biomechanics. On the other hand, soft actuators possess big advantages in comparison with the rigid ones. The materials used give them an advantage in geometry, cost, etc. Yet, the development of this new technology is not fully understood due to the material properties in the manufacturing process. 3D printing is seen as one of the most feasible manufacturing processes for this new technology. However, the information regarding the topic is limited. This study will focus into the characterization of 3D printed soft pneumatic actuator using as material silicone, especially in how the properties change when 3D printed with different printing orientations. Simulations were run using ANSYS and the results showed that the bellow printed at 90° has a higher resistance in the pressure applied and the 45° has a bigger deformation with a lower pressure.